Development of Smart Monitoring and Control System for Standalone Microgrids with PV Generation based on Everyday Power Consumption - Chun, Kyunghan; Koo, Bonhyeok; Lee, Dongsu; Kim, Bonghwan (International Journal of Engineering and Technology, 2018)
In this paper, we propose a development of smart monitoring and control (SMC) system for Microgrids (MGs) with photovoltaic (PV) generation based on everyday power consumption.Â Since their introduction, microgrid systems have attracted both the utility and public interest as they represented autonomous structures for generating, delivering, and distributing clean and sustainable electric energy to loads and/or utility grids. A microgrid system is generally defined as an independent combination of generating units, storage units, and loads, and can be interconnected to a utility grid as a single entity. We develop SMC for a microgrid with PV generation based on the everyday power consumption, so the microgrid can be operated within specification and prevented from the battery over-discharging. As a result, the battery lifetime also keeps longer.Â Â